The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1158/1535-7163.mct-08-0361
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition enhances anthocyanin-induced apoptosis in hepatocellular carcinoma

Abstract: Anthocyanins extracted from the berries of Phillyrea latifolia L., Pistacia lentiscus L., and Rubia peregrina L., three evergreen shrubs widely distributed in the Mediterranean area, were examined for their antioxidant and anticancer activity. The P. lentiscus anthocyanins showed the highest H 2 O 2 and 1,1-diphenyl-2-picrylhydrazil radical scavenging effects, indicating that these compounds can be considered as an alternative source of natural antioxidants for food and pharmaceutical products. Here, we also r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 46 publications
(60 reference statements)
8
60
0
1
Order By: Relevance
“…Our results show that 3-MA down-regulates the expression of Beclin-1 and LC3-I and inhibits the conversion of LC3-I into LC3-II, as well as decreasing the formation of acid vesicles in the cytoplasm of SHG-44 glioma cells. Moreover, 3-MA enhances MG-132-induced cell death and the number of cells in G 2 /M phase, indicating that autophagy has a protective effect on SHG-44 glioma cells, which is consistent with previous studies reporting that inhibition of autophagy enhances or accelerates cell death in malignant tumors [35,36] or reverses tumor cells' resistance to apoptosis [37] .…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that 3-MA down-regulates the expression of Beclin-1 and LC3-I and inhibits the conversion of LC3-I into LC3-II, as well as decreasing the formation of acid vesicles in the cytoplasm of SHG-44 glioma cells. Moreover, 3-MA enhances MG-132-induced cell death and the number of cells in G 2 /M phase, indicating that autophagy has a protective effect on SHG-44 glioma cells, which is consistent with previous studies reporting that inhibition of autophagy enhances or accelerates cell death in malignant tumors [35,36] or reverses tumor cells' resistance to apoptosis [37] .…”
Section: Discussionsupporting
confidence: 92%
“…[27][28][29][30] Hepatitis B virus and hepatitis C virus infections, liver cirrhosis and other inflammation diseases have been examined as potential risk factors for ICC, 31,32 and also potential factors for induction of autophagy. During growth of ICC, tumor cells periodically outstrip in the vasculature, resulting in narrowing blood vessels that causes nutrient starvation and low oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, autophagy had no effect neither on the etoposide-induced apoptosis under hypoxia, nor on the protection conferred by hypoxia. The inhibition of the expression of Atg5 gene with siRNA has already been reported to promote resistance to chemotherapy [51,52]. However, it has been reported that Atg5 might be cleaved by calpains and truncated Atg5 could stimulate apoptosis by direct interaction with Bcl-XL in the mitochondrial outer membrane [53].…”
Section: Discussionmentioning
confidence: 99%